2018
DOI: 10.3847/1538-4357/aaa973
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Non-universal Stellar Initial Mass Function. Insights from HST Optical Imaging of Six Ultra-faint Dwarf Milky Way Satellites

Abstract: Using deep observations obtained with the Advanced Camera for Surveys (ACS) on board the Hubble Space Telescope (HST), we demonstrate that the sub-solar stellar initial mass function (IMF) of six ultra-faint dwarf Milky Way satellites (UFDs) is more bottom light than the IMF of the Milky Way disk. Our data have a lowermass limit of ∼0.45 M e , while the upper limit is ∼0.8 M e , set by the turnoff mass of these old, metal-poor systems. If formulated as a single power law, we obtain a shallower IMF slope than t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
109
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 48 publications
16
109
3
Order By: Relevance
“…More recent analyses have complicated this picture. Gennaro et al (2018b) measured the IMFs for the full sample of six UFDs from Brown et al (2014), confirming that each galaxy has an IMF slope shallower than Salpeter when fit with a power law. However, when describing the IMF as a log-normal function (Chabrier 2003), the parameters for the UFDs are consistent with the Milky Way IMF.…”
Section: Initial Mass Functionsmentioning
confidence: 77%
“…More recent analyses have complicated this picture. Gennaro et al (2018b) measured the IMFs for the full sample of six UFDs from Brown et al (2014), confirming that each galaxy has an IMF slope shallower than Salpeter when fit with a power law. However, when describing the IMF as a log-normal function (Chabrier 2003), the parameters for the UFDs are consistent with the Milky Way IMF.…”
Section: Initial Mass Functionsmentioning
confidence: 77%
“…Recent measurements with the Hubble Space Telescope by Gennaro et al (2018b) of UFD satellite galaxies, as an extension of the study by Geha et al (2013), have suggested a possible gwIMF variation in these galaxies in the stellar-mass range (0.4−0.8 M ). The authors, however, mentioned that a larger data sample is needed to improve the reliability of the presented results.…”
Section: Ultra-faint Dwarf Galaxiesmentioning
confidence: 80%
“…For the case of Leo P, the known extent and baryonic matter in Leo P and the flat (non-rising) part of the rotational curve are UFDs shown by the coloured points from Gennaro et al (2018b). The IGIMF1 models (given by two slopes α 1 = 1.3 and α 2 = 2.3) are represented by the horizontal green line.…”
Section: Implications For the Btfr And The Cmdmentioning
confidence: 99%
“…Galaxies with a high star formation rate are known to be producing stellar populations overabundant in massive stars (Gunawardhana et al 2011), while galaxies with a low star formation rate show a deficit of massive stars (Lee et al 2009;Watts et al 2018). Old, dormant galaxies also show significant variations of their stellar populations: elliptical galaxies may be dominated by very low mass stars (van Dokkum & Conroy 2010), while faint diffuse dwarf galaxies have a deficit of low mass stars (Gennaro et al 2018) when compared to the canonical stellar population (Yan et al 2017;Jeřábková et al 2018).…”
Section: The Properties Of Ngc 1052-df2 At Different Distancesmentioning
confidence: 99%